Embedded programming with modern C++ cookbook practical recipes to help you build robust and secure embedded applications on Linux - Viarheichyk, Igor (Packt Publishing, 2020)
This book is a collection of practical examples for understanding how embedded development is different from other desktop application development. You'll learn to build an embedded application and use specialized memory and custom allocators. By the end of the book, you'll be able to build robust and secure embedded applications with C++20
Keywords: C -- Programmiersprache; Eingebettetes System; COMPUTERS / Microprocessors; COMPUTERS / Hardware / Peripherals